The ANTARA and TEMPO Media’s Framing Strategy Differences in Framing the Omnibus Law Ratification Issue - Rize Rahmi; Sawirman Sawirman; Aslinda Aslinda (Ranah: Jurnal Kajian Bahasa, 2021)
In this research, the authors compared the framing strategy used by the ANTARA media and TEMPO media for the issue of the ratification of the Omnibus Law on Job Creation. This research was conducted descriptively with comparative qualitative approach. A qualitative document procedure was applied in collecting the data. Fairclough's framework of Critical Discourse Analysis and the framing analysis model by Pan and Kosicki (1993) were combined to analyze the data. The result of the data analysis is presented in the table and the interpretation form. The result shows that TEMPO's framing strategy is more clearly defined, while ANTARA's strategy is less clear. In building a negative or positive representation, TEMPO Media tries to present information supported by many sources. Then, the use of images in TEMPO news supports the truth of information, while the use of images in ANTARA media improves the quality of information sources. The five news stories from ANTARA media selected in this study always use the face image of the selected informant as a source of news information. AbstrakPada penelitian ini, penulis membandingkan strategi pembingkaian yang digunakan media ANTARA dan TEMPO dalam membingkai isu pengesahan Omnibus Law Cipta Kerja. Penelitian ini dilakukan secara deskriptif dengan pendekatan komparatif kualitiatif. Prosedur dokumen kualitatif diterapkan dalam pengumpulan data. Kerangka analisis wacana kritis Fairclough dan model analisis pembingkaian oleh Pan dan Kosicki (1993) digabungkan untuk menganalisis data. Hasil analisis data disajikan dalam bentuk tabel dan interpretasi. Hasil penelitian menunjukkan bahwa strategi pembingkaian TEMPO lebih jelas, sedangkan strategi ANTARA kurang jelas. Dalam membangun representasi negatif atau positif, TEMPO mencoba menghadirkan informasi yang didukung oleh banyak sumber. Kemudian, penggunaan gambar dalam berita TEMPO mendukung kebenaran informasi, sedangkan penggunaan gambar di media ANTARA meningkatkan kualitas sumber informasi. Kelima berita dari media ANTARA yang dipilih dalam penelitian ini selalu menggunakan foto sumber informasi yang terpilih pada berita.